Islamic Terminology: Translation and Context - Abdullah Khalel, Lames (Opción, 2019)
Islamic texts such as The Glorious Quran, The Nobel Prophetic Tradition, and the wealth of literatures written by Muslim scholars throughout the centuries, have been preserved in Arabic, their original language. Readers of Islamic literatures, written in non-Arabic languages, are not always certain that the translated Arabic terminologies have indeed kept their intended meanings. This challenge is also observed in the translated texts from Arabic to other languages. Pointing to this challenge does not make the Islamic non-Arabic texts useless; it simply makes them not fully reliable. Readers accordingly should always consult the Arabic texts and their correspondent contexts; oth- erwise their conclusion may very well be wrong. The reason for such chal- lenge stems from the limitations of the non-Arabic languages compared to the Arabic language; its richness, grammar, and eloquence. Another reason for such challenge is that some Arabic terms were taken out of their intended con- texts; something that led to distortion and corruption of the intended mean- ing. Readers often are left to reach the wrong understanding. In this paper, four Arabic terminologies were chosen from The Quran and analyzed within their original Arabic linguistic meaning, their Islamic definition, ‘Istelah’ and within the context of each term wherever it may appear. The benefit of such analysis is to provide the new reverts to Islam and those who teach Islam to non-Arab people, a frame of reference through which their comprehension of the text they read is in line with what the original Quranic context had intend- ed the reader to grasp. Clarifying some of the misconceptions, about Islam, that have spread outside the Muslim World, and even within it, is another benefit of this work. The goal is to better understand Islam as a way of life, and to hopefully give a clearer opportunity for future generations to coexist peacefully.